PENDAMPINGAN KELOMPOK USAHATANI POLA DUSUNG DALAM MENYIKAPI DAMPAK PERUBAHAN IKLIM TERHADAP PRODUKSI TANAMAN PALA DI NEGERI MAMALA KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Jan Willem Hatulesila; Thomas Melianus Silaya; Nirawati Nirawati (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The traditional farming pattern of dusung as a form of agroforestry in the Maluku archipelago, namely Ambon Island, Seram Island and Lease Islands, has taken place and developed simultaneously with the socio-cultural life of the local community as a form of local wisdom. As an effort to increase the production of nutmeg commodities as one of the superior commodities in the local market, the national market and even to the point of being traded in the international market, the efforts to assist farmer groups of dusung patterns need and always from the impact of climate change that occurs so that the cultivation and maintenance of nutmeg crops by dusung farmers will provide good results to increase the income and income of nutmeg farmers themselves. In this mentoring and strengthening activity of nutmeg farming groups, there are also various important inputs as solutions to a number of problems related to farming patterns and various encouragements to farmers to be able to innovate starting from the cultivation, handling and maintenance processes to the utilization of product products in the form of diversification of nutmeg products.